Mild traumatic brain injury increases engagement in criminal behaviour 10 years later: a case–control study - Theadom, Alice; Meehan, Lisa; McCallum, Sandra; Pacheco, Gail (Frontiers in Psychiatry, 2023)
Sustaining a mild traumatic brain injury (mTBI) has been linked to increased criminal behaviour in later life. However, previous studies have not controlled for the number of injuries, gender, social deprivation, impact of past behaviour, or link to offence type. This study aims determine if people who experienced a single or multiple mTBI have increased risk of criminal behaviour ten years post-injury than matched orthopaedic controls. This was a case control study of adults (aged≥16years) who experienced a medically diagnosed mTBI and controls who experienced a lower limb fracture (with no TBI) over a 12-month period (01/01/2003-31/12/2003). Participants were identified within Stats New Zealand’s Integrated Data Infrastructure (national database including health and justice records). Participants who experienced a subsequent TBI (post-2003), who were not resident in New Zealand, and who died by 2013 were excluded. Case and controls were matched by age, sex, ethnicity, deprivation index and pre-injury criminal history. The study included N=6,606 mTBI cases and N=15,771 matched trauma controls. In the 10 years after injury, people experiencing a single mTBI group had significantly higher numbers of violent charges (0.26 versus 0.21, p<0.01) and violent convictions (0.16 versus 0.13, p<0.05) but not for all court charges and convictions. Analysis of those with a history of prior mTBIs yielded larger effects, with significantly higher numbers of violent charges (0.57 versus 0.24, p<0.05) and violent convictions (0.34 versus 0.14, p<0.05). For males, the single mTBI case group had a significantly higher number of violent charges (0.40 versus 0.31, p<0.05) and violent convictions (0.24 versus 0.20, p<0.05) but this was not observed for females or all offence types. Experiencing multiple mTBIs over the lifetime increases the number of subsequent violence-related charges and convictions but not for all offence types in males but not for females. These findings highlight the need for improved recognition and treatment of mTBI to prevent future engagement in antisocial behaviour.